Dampak El Nino Terhadap Produktivitas Pertanian Analisis Sistematis Ketahanan Pangan di Wilayah Tropis - Nelwan Satrio Gunawan; Muhammad Izzudin; Atiawati Atiawati; Cahaya Latifa; Fadia Febrianti; Deris Desmawan (LPPM Universitas Labuhanbatu, 2024)
El Niño is a climate phenomenon that occurs due to atmospheric circulation indicated by increasing sea surface temperatures. El Niño causes changes in weather patterns, including a significant decrease in rainfall, resulting in prolonged drought and a decrease in agricultural productivity, especially in tropical regions such as Indonesia. This study aims to explore the impact of El Niño on agricultural productivity and find effective solutions to overcome related problems. The method used in this study is library research to analyze various literature from various sources such as journals and official reports related to the research topic. The results of the study show that El Niño results in a decrease in agricultural productivity including crop yields of up to 40% in several regions. This has an impact on increasing food prices and dependence on imports, thus worsening food security in Indonesia. The application of efficient irrigation and the use of information technology can be a solution to overcome drought and manage air resources. Digital education also plays an important role in overcoming these conditions. In addition, collaboration between farmers, the government, and the technology sector needs to be carried out to maintain the sustainability of agriculture and food security in facing the challenges of global climate change. In conclusion, appropriate adaptation measures are needed to mitigate the negative impacts of El Niño on the agricultural sector and ensure sustainable food security.